Alternative teaching materials for distance learning for student with special needs - Ishartiwi Ishartiwi; Rendy Roos Handoyo; Wening Prabawati; Adi Suseno (Universitas Negeri Yogyakarta, 2022)
This research aimed at describing teachers' needs in developing distance learning material from the aspect of physical forms, teaching material delivery, and obstacles faced by teachers. Through a survey of 115 special education teachers in Yogyakarta, The data were obtained through an open questionnaire and analyzed using descriptive quantitative approach. The result shows that alternative teaching materials needed were in the form of printed, audio, and electronic modules. Modules contained daily life activities is aimed to increase the independence of the students. The scope that is needed is an understanding of the concept in the cognitive aspect. Teachers need modules that can be studied independently by students with special needs. The presentation of the material that is most needed is in the form of videos and animated images as aids to make it easier to understand the material. Module display is considered to have more varied and striking color combinations. The obstacles experienced by the teachers were due to the difficulty of identifying the various abilities of the students.